Improving the reliability of SRAM-based PUFs under varying operation conditions and aging degradation. (March 2021) - Saraza-Canflanca, P.; Carrasco-Lopez, H.; Santana-Andreo, A.; Brox, P.; Castro-Lopez, R.; Roca, E.; Fernandez, F.V.
Abstract: The utilization of power-up values in SRAM cells to generate PUF responses for chip identification is a subject of intense study. The cells used for this purpose must be stable, i.e., the cell should always power-up to the same value (either '0' or '1'). Otherwise, they would not be suitable for the identification. Some methods have been presented that aim at increasing the reliability of SRAM PUFs by identifying the strongest cells, i.e., the cells that more consistently power-up to the same value. However, these methods present some drawbacks, in terms of either their practical realization or their actual effectiveness in selecting the strongest cells at different scenarios, such as temperature variations or when the circuits have suffered aging-related degradation. In this work, the experimental results obtained for a new method to classify the cells according to their power-up strength are presented and discussed. The method overcomes some of the drawbacks in previously reported methods. In particular, it is experimentally demonstrated that the technique presented in this work outstands in selecting SRAM cells that are very robust against circuit degradation and temperature variations, which ultimately translates into the construction of reliable SRAM-based PUFs.